2011
DOI: 10.1021/jp207856p
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Flexibility Influences Degree of Hydration of Nucleic Acid Hybrids

Abstract: Four nucleic acid duplexes-DNA/RNA hybrid, RNA/DNA hybrid, RNA duplex, and DNA duplex-were studied under molecular crowding conditions of osmolytes. Destabilization of duplexes (ΔΔG°(25)) indicated that the ΔΔG°(25) values of hybrids were intermediate between those of DNA and RNA duplexes. In the presence of polyethylene glycol 200, the ΔΔG°(25) values were estimated to be +3.0, +3.5, +3.5, and +4.1 kcal mol(-1) for the DNA duplex, DNA/RNA hybrid, RNA/DNA hybrid, and RNA duplex, respectively. Differences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 91 publications
3
29
0
Order By: Relevance
“…The G-quadruplexes formed by RNAs are generally more stable than those formed by equivalent DNA sequences (21–23). Our previous studies indicate that stabilities of G-quadruplexes are higher in the presence of high concentration of cosolute, which might mimic cell-like molecular crowding condition, and encapsulated conditions than in diluted solution (24,25), whereas canonical secondary structures are destabilized in the presence of cosolute, especially solutes decreasing water activity (26,27). In addition, we recently performed that RNA G-quadruplex formed in ORF of mRNA suppressed translation elongation in vitro and reduced protein expression in cells (28).…”
Section: Introductionmentioning
confidence: 98%
“…The G-quadruplexes formed by RNAs are generally more stable than those formed by equivalent DNA sequences (21–23). Our previous studies indicate that stabilities of G-quadruplexes are higher in the presence of high concentration of cosolute, which might mimic cell-like molecular crowding condition, and encapsulated conditions than in diluted solution (24,25), whereas canonical secondary structures are destabilized in the presence of cosolute, especially solutes decreasing water activity (26,27). In addition, we recently performed that RNA G-quadruplex formed in ORF of mRNA suppressed translation elongation in vitro and reduced protein expression in cells (28).…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, the formation of DNA (and perhaps RNA) three-way junctions (TWJ) [25], [26], of G-quadruplex structures [27], [28] and of DNA triple helices [29] are favored in crowded solutions. Next to the excluded volume effect, hydration has been identified as a crucial factor for the stability of RNA molecules in crowded solutions with opposite effects on the stabilities of RNA tertiary and secondary structures [23], [30], [31]. Neutral cosolutes can stabilize the water release reaction of RNA 3D-folds while at the same time disfavor the water-uptake reaction of Watson-Crick base pairs [23].…”
Section: Introductionmentioning
confidence: 99%
“…We concluded that crowding conditions induced by the organelle-mimicking liposomes had no effect on structures or stabilities of canonical and non-canonical DNA structures. It has been reported that molecular crowding decreases the stability of a duplex and increases that of the G-quadruplex by decreasing water activity (1922). The water activities of solution without liposome and with 2.0 mM IM, NM or ER liposomes were not significantly different ( a w = 0.993, where a w is water activity estimated by vapour pressure osmometry).…”
Section: Resultsmentioning
confidence: 99%
“…We extracted thermodynamic parameters from melting curves as described previously (1922). The value of Δ G ° 25 (free energy change of the formation of a G-quadruplex at 25°C) for 1cG 3 increased from −3.1 to −1.2 kcal mol −1 when the concentration of POPC was increased from 0 to 2.0 mM (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation